Reference quantitative transcriptome dataset for adult Caenorhabditis elegans - Piovesan, Allison (Data Brief, 2019)
Caenorhabditis elegans is a nematode widely used in biology and genomics as a model organism. We provide an integrated, quantitative reference map for the transcriptome of whole, wild type Bristol N2 strain C. elegans worms. The map has been obtained by meta-analysis of 110 gene expression profiles available in Gene Expression Omnibus (GEO) repository and integrated using the computational biology tool Transcriptome Mapper (TRAM). Following probe assignment to the relative locus and intra- and inter-sample normalization (in particular using the scaled quantile method), a mean, consensus reference value is provided for 45,932 transcripts, along with standard deviation. Expression values are all mapped in the context of genomic coordinates. The map provides easy access to relationships among expression values of different genes in this standard condition, highlights genomic segments with relatively high over-/under-expression and may serve as a reference to test for gene expression variation for both individual genes and the whole transcriptome in specific biological conditions (e.g. mutated strains or differently grown worms).